Social Entrepreneurship In MSME Development - YATMINIWATI, Mimin; SETYOBAKTI, Moh. Hudi; SULISTYAN, Riza Bahtiar; ERMAWATI, Emmy (PT Keberlanjutan Strategis Indonesia, 2021)
The creative industry through community-based industry on the scale of MSMEs, has developed quite well. The creative industry has the opportunity to continue to increase, because the industry is responsive to absorb the accumulation of social phenomena in society and pour it into the context of products and services. The problems faced by MSMEs are still homework, the problems include fulfilling the market aspect, which is caused by the availability of the goods produced. This study aims to obtain problem information and the right solution approach in answering the existing problems. The results of the study indicate that the problem of human resource availability can be done with alternative solutions in the form of a social entrepreneurship approach with the involvement of the community around the industry